Rent-Seeking Practices in the Housing Development Approval Process - Abdul-Rashid Abdul-Aziz; Suhaila Ali (Kajian Malaysia, 2021)
The lengthy, uncertain and onerous planning approval process in various countries around the world has prompted frustrated housing developers to seek influence by paying off approving officials. A research was conducted in Malaysia to investigate in greater detail this rent-seeking phenomenon by asking six fundamental questions. Rich data were obtained by interviewing 22 housing developers and consultants who work for them. Developers engage in rent-seeking behaviours to overcome genuine and artificial hurdles when applying for development approval. All approving agencies, though not all their staff, reciprocate to such behaviours. The monetary value of the payoffs depend on the rank of the public actor and project features. The higher the office holder is, the larger is the expected pay-off. Big and complex development projects in urban centres have a higher pay-off tag. Low value items television sets and car repairs serve to support normal lifestyle whereas high value items such as golfing and holiday trips support lavish lifestyle. Establishing good rapport is a prerequisite to the rent seeking and giving exchange. Elements which help foster reciprocity by state actors to housing developers’ rentseeking behaviours include low civil servant salary and high living cost, and weak punitive action. Common ethnicity facilitates nuanced communication by the latter, but common religion may dampen the former’s enthusiasm to accept any payoffs. Eventually house buyers and the general public are the casualties by virtue of higher house prices and substandard infrastructure. Given the combination of inherent features of the planning system and certain elements that impinge on state actors both of which promote rent-seeking practices, a realistic law enforcement solution is to prioritise illicit market-state exchanges involving grossly distorting rent extraction and pecuniary rewards of significant magnitude rather than total eradication of the practice.